Model Pengembangan Aplikasi â€Ingat Minum Obat ARVâ€ Berbasis Android sebagai Pengingat Minum Obat pada ODHA - Fatimatuzahro Fatimatuzahro; Bagoes Widjanarko; Zahroh Shaluhiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study explores the need for drinking reminders for ODHA in the form of an application and to develop an Android-based application as an information medium and reminder to take medication for ODHA in Pekalongan Regency. The method used is research and development with the ADDIE development model with the stages of needs analysis, concept design, and application development. The study results a show that application features are needed based on needs analysis. The application design is compiled, and validation tests are carried out by ODHA and counselors through Focus Group Discussions (FGD). Application design development through validation tests by material experts, academics, and practitioners in HIV/AIDS. Applications need revisions in design, colors, icons, menus, sub-menus, content, appearance, editorial, notification ringtones, and connection to peer support groups. The model feasibility validation test results stated that the application